Bovine Lactoferrin Enhances TLR7-Mediated Responses in Plasmacytoid Dendritic Cells in Elderly Women: Results From a Nutritional Intervention Study With Bovine Lactoferrin, GOS and Vitamin D - Marloes van Splunter; Olaf Perdijk; Henriëtte Fick-Brinkhof; Anouk L. Feitsma; Esther G. Floris-Vollenbroek; Ben Meijer; Sylvia Brugman; Huub F. J. Savelkoul; Els van Hoffen; R. J. Joost van Neerven; R. J. Joost van Neerven (Frontiers in Immunology, 2018)
During aging the immune system is dysregulated. Especially plasmacytoid dendritic cells (pDCs) and myeloid DCs (mDCs) have reduced Toll like receptor (TLR)-mediated responses resulting in increased susceptibility to infections. Consumption of bovine lactoferrin (bLF) has been shown to reduce infections with viruses. Galacto-oligosacharides (GOS) and vitamin D are associated with reduced pro-inflammatory cytokine levels in serum, and increased TLR7/8 responses, respectively. A double-blind placebo-controlled nutritional intervention study in elderly women was performed, to investigate the potential of bLF, GOS, and vitamin D to restore TLR responsiveness of pDCs and mDCs and to reduce inflammatory markers in serum. The nutritional intervention group (n = 15) received bLF for 3 weeks, followed by 3 weeks of bLF + GOS, and subsequently 3 weeks of bLF + GOS + vitamin D. The placebo group (n = 15) received maltodextrin for 9 weeks. Every 3 weeks, blood was collected and TLR responses of pDCs and mDCs, and inflammation-related markers in serum were measured. After 3 weeks of bLF supplementation, increased TLR7/8 and TLR1/2 responses were observed in pDCs of the nutritional intervention group compared to the placebo group. When the effects of the entire nutritional intervention were investigated, increased TLR1/2 mediated responses in mDCs were observed, and in serum sVCAM tended to decrease. Finally, based on the RAND-36 questionnaire physical function tended to improve in the intervention group. Since especially TLR7-mediated responses in pDCs were enhanced after bLF supplementation compared to placebo, this suggests that bLF may contribute to antiviral responses mediated by pDC in elderly women.Clinical trial registry number: NCT03026244, clinicaltrials.gov: